Influence of CYP3A5 genotypes on tacrolimus dose requirement: age and its pharmacological interaction with ABCB1 genetics in the Chinese paediatric liver transplantation. (May 2015) - Yang, T.‐H.; Chen, Y.‐K.; Xue, F.; Han, L.‐Z.; Shen, C.‐H.; Zhou, T.; Luo, Y.; Zhang, J.‐J.; Xia, Q.
Summary: Aim: The purpose of the study was to evaluate the impact of single nucleotide polymorphisms (SNPs) of Cytochrome P450 ( CYP ) 3A5 and adenosine triphosphate‐binding cassette B1 ( ABCB1 ) genotypes on TAC pharmacokinetics in Chinese paediatric patients. Method: A total of 136 Chinese paediatric liver recipients (R) and their donors (D) were divided into groups according to their CYP3A5 genotypes [expression of *1 allele: expressor (EX) or non‐expressor (NEX)]. Result: Both recipient and donor CYP3A5 *1 alleles had impacts on the TAC pharmacokinetics after liver transplantation. EX‐R/EX‐D recipients required a significantly higher TAC daily dose compared with NEX‐R/NEX‐D (0.24 ± 0.08 vs. 0.14 ± 0.06 mg/kg/day, p < 0.01). Age was also an independent factor on TAC requirement. Compared with EX‐R/EX‐D, non‐expressor infants or recipients over 3‐years old needed < 0.2 mg/kg/day. None of the ABCB1 SNPs (1236C>T, 2677G>A/T, 3435C>T) had an impact on TAC pharmacokinetics. However, EX‐R/EX‐D recipients bearing the ABCB1 1236‐CC genotype required a much higher TAC dose than those without this genotype (0.23 vs. 0.18 mg/kg/day, p < 0.01), who required a similar TAC dose to that of NEX‐R/NEX‐D children. Furthermore, EX‐R/EX‐D with ABCB1 1236‐CC recipients exhibited an markedly higher incidence of acute rejection and transplant‐related infections clinically. Conclusion: CYP3A5 and ABCB1 ‐1236 genotyping, in addition to recipient age, are necessary for establishing a more accurate TAC dosage regimen in paediatric liver recipients. We should be cautious regarding the treatment of paediatric recipients with both CYP3A5 ‐expressor and ABCB1 1236‐CC genotypes with TAC, as these patients are more susceptible to acute rejection and infection.